Dual Targeting EGFR and STAT3 With Erlotinib and Alantolactone Co-Loaded PLGA Nanoparticles for Pancreatic Cancer Treatment - Bao, Shihui; Zheng, Hailun; Ye, Jinyao; Huang, Huirong; Zhou, Bin; Yao, Qing; Lin, Guangyong; Zhang, Hailin; Kou, Longfa; Chen, Ruijie (Frontiers in Pharmacology, 2021)
Pancreatic cancer (PC) is one of the most common malignancies and also a leading cause of cancer-related mortality worldwide. Many studies have shown that epidermal growth factor receptor (EGFR) is highly expressed in PC, which provides a potential target for PC treatment. However, EGFR inhibitors use alone was proven ineffective in clinical trials, due to the persistence of cellular feedback mechanisms which foster therapeutic resistance to single targeting of EGFR. Specifically, the signal transducer and activator of transcription 3 (STAT3) is over-activated when receiving an EGFR inhibitor and is believed to be highly involved in the failure and resistance of EGFR inhibitor treatment. Therein, we hypothesized that dual inhibition of EGFR and STAT3 strategy could address the STAT3 induced resistance during EGFR inhibitor treatment. To this end, we tried to develop poly (lactic-co-glycolic acid) (PLGA) nanoparticles to co-load Alantolactone (ALA, a novel STAT3 inhibitor) and Erlotinib (ERL, an EGFR inhibitor) for pancreatic cancer to test our guess. The loading ratio of ALA and ERL was firstly optimized in vitro to achieve a combined cancer-killing effect. Then, the ALA- and ERL-co-loaded nanoparticles (AE@NPs) were successfully prepared and characterized, and the related anticancer effects and cellular uptake of AE@NPs were studied. We also further detailly explored the underlying mechanisms. The results suggested that AE@NPs with uniform particle size and high drug load could induce significant pancreatic cancer cell apoptosis and display an ideal anticancer effect. Mechanism studies showed that AE@NPs inhibited the phosphorylation of both EGFR and STAT3, indicating the dual suppression of these two signaling pathways. Additionally, AE@NPs could also activate the ROS-p38 axis, which is not observed in the single drug treatments. Collectively, the AE@NPs prepared in this study possess great potential for pancreatic cancer treatment by dual suppressing of EGFR and STAT3 pathways and activating ROS-responsive p38 MAPK pathway.